Parent-child relationships in the united arab emirates - Joana Novaes Machado Stocker; Khairia Ghuloum Ali Mohamed Hassan Ali (INFAD, 2014)
The family plays a crucial role throughout the child’s life, being responsible for raising him/her according to certain values, beliefs, attitudes, and behaviors accepted both in the family and respective society/culture. Specifically, parent-child relationship is proved to affect interpersonal skills and relationships, behaviors, academic achievement and professional, amongst others. Research shows that for a healthy, positive, and adaptive development, a close, warm, supportive, and accepting parent-child relationship should have place. In this research, it was aimed to analyze parent–child relationships in a very specific and idiosyncratic context that has been under lots of recent economic, social, cultural, and, we assume, familiar changes and that has been understudied: United Arab Emirates. Concretely, we explored Emirati parents’ perceptions on seven main dimensions of parent–child relationships: parental support and satisfaction, involvement, communication, limiting setting, autonomy and role orientation. The participants were 122 Emirati parents, mostly mothers (73.8%) and married (96.3%), with ages between 21 and 63 years old (M=35.98, SD= 9.172), and with different levels of education (50% of the parents have a bachelor degree). The instrument used was the Parent-Child Relationship Inventory (PCRI), a standardized instrument published by the Western Psychological Services that integrates 78 items with a 4-point agreement Likert scale, divided by the dimensions previously presented plus a validity indicator (social desirability). All the questionnaires were individually administered, and descriptive and correlational analyses were performed to understand Emirati parents’ attitudes towards their children and explore how the PCRI dimensions interrelate. Overall, Emirati parents perceive themselves as satisfied, involved and communicative with their children, meanwhile they face some difficulties in establishing limits and promoting autonomy, and tend to accept and apply within their families traditional gender roles. The dimensions of the PCRI exhibit a global pattern of positive and moderate intercorrelation, consistent with the theoretical background of this instrument.